Stability-based system for bearing fault early detection. (15th August 2017) - Diaz, Moises; Henriquez, Patricia; Ferrer, Miguel A.; Pirlo, Giuseppe; Alonso, Jesus B.; Carmona-Duarte, Cristina; Impedovo, Donato
Highlights: Novel Stability-based system for early bearing fault detection. Novel use of Dynamic Time Warping and Direct Matching Point techniques. Findings on continuous monitoring of vibration signals with low false alarms for faults Findings on two publicly available databases under several machining conditions. Abstract: This paper presents a new and straightforward system for bearing fault detection. The system computes the stability of two vibration signals by using the direct matching points (DMP) of an elastic and non-linear align function. It is able to find discriminant properties in the stability of fault-free and faulty bearing vibration signals from the early and late stages of the fault in critical bearing parts. Because training data constitutes one of the critical challenges in most expert and intelligent systems, one of the novelties of the proposed stability-based system is that it requires neither training nor fine-tuning. A significant impact on the robustness of the system is demonstrated using two publicly available vibration signal databases under several load conditions, with real faults, during multiple machine working states. Experimental results validate the use of the proposed stability-based system for predictive maintenance in bearings.